DYNAMICS OF DEVELOPMENT OF LITHOFLUID OIL AND GAS SYSTEMS IN THE CRETACEOUS DEPOSITS OF THE WESTERN CENTRICLINAL OF THE BLACK SEA MEGADEPRESSION - Hryhorchuk, K.; Hnidets, V.; Wojcickyu, Z. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
On the basis of modeling the dynamics of the catagenesis of the Cretaceous deposits, the lateral heterogeneity of the history of their catagenesis within the western part of the Black Sea megadepression, caused by the tectonic regime of the blocks separated by the Golitsyn, Sulino-Tarkhankutsky, Gubkino-Donuzlavsky sublatitudinal faults, was established. The spatio-temporal features of the development of reservoirs and migration paths of hydrocarbon fluids have been established, the predicted zones of oil and gas accumulation have been localized. There are four types of lithogenetic reservoirs, which differed in the time of formation, structural features, fluid regime and the nature of oil and gas saturation.In the first cycle of catagenesis, the generation center was localized mainly in the sediments of the Lower Albian (t 80–100 оС), in the second – the Middle Albian (t 100–120 оС), in the third – the Upper Albian (t 130–150 оС).Given a certain difference in the situations of sedimentation of these stratigraphic units, the composition and content of scattered organic matter in the sediments were different. This, as well as the different generation temperatures, obviously caused the specific composition of hydrocarbon fluids formed during individual cycles of catagenesis. Along the migration pathways and during structural changes, these fluids were mixed, multicomponent systems were formed, and the composition of hydrocarbons changed.The possibility of the existence of subvertical "vein" areas of oil and gas accumulation with a width of up to 10 km and a height of 1,5–2,0 km is argued. Such reservoirs, on the one hand, may contain deposits and, on the other hand, supply hydrocarbons to overlying traps. Given the nature of oil and gas accumulation, the potential resources and, consequently, the prospects for oil and gas in the region can be much higher.
Keywords: Black Sea megadepression; Cretaceous deposits; catagenesis; oil and gas potential